2022
DOI: 10.1186/s40792-022-01378-w
|View full text |Cite
|
Sign up to set email alerts
|

A case of breast squamous cell carcinoma following breast augmentation with liquid silicone injection after 16 years

Abstract: Background Breast augmentation has been linked to various complications, including cancerous tumors. The majority type of breast cancer associated with breast augmentation is adenocarcinoma. Primary squamous cell carcinoma (SCC) of the breast is extremely rare in both augmented and non-augmented women. Due to the low incidence, the possible origin and the mechanism of carcinogenesis of the breast SCC are not well understood. Here, we report a rare case of pure SCC 16 years after breast augmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The patient reported by Soni et al was pregnant and underwent capsulectomy, implant removal, and mastectomy during her pregnancy, but chemotherapy and radiation were given after the pregnancy [ 14 ]. Four cycles of epirubicin, cyclophosphamide therapy, and four cycles of docetaxel therapy were used by Toyonaka et al [ 21 ]. Liu et al reported using gemcitabine combined with carboplatin followed by radiation therapy with the subsequent addition of capecitabine.…”
Section: Resultsmentioning
confidence: 99%
“…The patient reported by Soni et al was pregnant and underwent capsulectomy, implant removal, and mastectomy during her pregnancy, but chemotherapy and radiation were given after the pregnancy [ 14 ]. Four cycles of epirubicin, cyclophosphamide therapy, and four cycles of docetaxel therapy were used by Toyonaka et al [ 21 ]. Liu et al reported using gemcitabine combined with carboplatin followed by radiation therapy with the subsequent addition of capecitabine.…”
Section: Resultsmentioning
confidence: 99%
“…Malignant squamous transformation is known to develop in wounds involved with chronic inflammation. However, there is no experimental or clinical evidence to support expected findings of epithelialization of the implant capsule and subsequent squamous dysplasia in the pathologic evaluation of capsulectomy specimens ( 13 15 ). In this case study, we present a rare case of SCC of the breast with a rare mechanism of onset.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to penile SCC, three incidences of breast SCC following liquid silicon injection have been reported. 13 , 14 , 15 , 16 The standard procedure for breast augmentation has changed from liquid silicon injection to prosthesis implantation. Breast SCC is a histologically rare form of breast cancer.…”
Section: Discussionmentioning
confidence: 99%